Non-Communicable Diseases and Adherence to Mediterranean Diet - Caretto, Antonio; Lagattolla, Valeria (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2015)
Non-communicable diseases (NCDs) also known as chronic diseases last for a long time and progress generally slow. Major non-communicable diseases are cardiovascular diseases, cancers, chronic respiratory diseases and diabetes. Unhealthy lifestyles and food behaviours play an important role for determining such diseases. The change in unhealthy behaviours or the maintenance of healthy lifestyles has enormous value in the reduction of diseases and longer life expectancy not only on an individual level but for the community as a whole. Recent meta-analyses reported Mediterranean diet to be an optimal diet when adopted as a whole, in order to preserve and maintain a good health status. A greater adherence score to the Mediterranean diet (2-point increase) was related to induce an 8% reduction in overall mortality, a 10% reduced risk of CVD and a 4% reduction in neoplastic diseases. However, there is no direct method in quantifying and evaluating adherence, therefore a large number of indirect indices in several studies have been proposed, with a last unifying score. Recently more and more e-health techniques such as web communication or desktop publishing (DVDs and so on) are being used, obtaining good results in the Mediterranean diet adherence. For successfully changing the unhealthy lifestyles and food behaviours of the population, interventions at all levels are needed with the cooperation of Institutions, mass media, agricultural and food industry and healthcare professionals guided by expert scientific societies.
Keywords: mediterranean diet